Imagem corporal, índice de massa corporal, perímetro da cintura, alteração da pressão arterial e intolerância à glicose entre os povos indígenas do Xingu, Brasil - Santos, Kennedy Maia dos [UNIFESP] (2016)
Objective: To assess body self-image, nutritional status and the cutoff points of body mass index (BMI) and waist circumference (WC) and the association with alteration in blood pressure (BP) and glucose intolerance (GI) among indigenous peoples of the Xingu, Brazil. Methods: Cross-sectional study that evaluated data from 131 individuals of Khisêdjê ethnicity with twenty years or more and 919 natives in the same age group, belonging to fourteen ethnic groups in the Xingu Indigenous Park (PIX), including Panará, who lived in the PIX up 1997. Data collection was carried out in the indigenous villages by trained professionals at different times: in 1999 (Suyá/Khisêdjê), 2000-2002 (ethnic groups of the Upper Xingu), 2006-2007 (Panará) and 2010 - 2011 (Khisêdjê). We collected data on BMI by weight and height, WC, blood pressure and fasting glucose, body self-image (only Khisêdjê) and physical activity (only Khisêdjê). Data analysis was performed using the chi-square, Student's t test, Kappa statistics, prevalence ratios by Poisson regression. To identify cutoff points of BMI and WC from which there was an increased prevalence of alteration in blood pressure and glucose intolerance was used the logistic regression, calculating the sensitivity, specificity and percentage of individuals correctly classified by BMI and WC according to percentiles 25, 50, 75, 90 and 95 and ROC curve analysis (receiver operating characteristic) to assess the accuracy of tests. Results: Among the Khisêdjê, satisfaction with body image was 61.8%, with no difference between sexes. There was good agreement between real and ideal self-image among men and women (p<0.001) but low correlation between real and ideal self-image and nutritional status. There was higher prevalence of dissatisfaction overweight among individuals with central obesity (PR = 2.76 and 95% CI: 1.10-6.92), overweight (PR = 2.77 and 95% CI: 1.19-6.47), among those with GI (PR = 2.44 and 95% CI: 1.19-5.01) and among subjects with average performance in trunk flexion test (PR = 7.53 95% CI: 1.37-41.31). In the analysis including indigenous PIX, the percentages of overweight and obesity were 39.7% and 7.8% respectively. The prevalences of hypertension and diabetes mellitus were 5.5% and 1.2%, respectively. There has been no trend of increased prevelence of GI and alteration in blood pressure according to the increase in WC values. As for BMI values between 32.0 and 32.9 kg/m2 were associated with higher prevalence of GI (OR = 12.26, 95% CI 2.25-66.65). Also, BMI values from 30.0 to 30.9 kg/m2 (OR = 3.59, 95% CI 1.21-10.61) and from 31.0 to 31.9 kg/m2 (OR = 6. 05, 95% CI 1.53-23.86) were associated with the occurrence of alteration in BP. The values of the X and Y axes regarding the intersection between the sensibility and sensitivity curves in predicting the GI for the WC test were respectively 89 cm and 0.54 for females, and 84.3 cm and 0.54 for males; in prediction of alteration BP values were respectively 85.7 cm and 0.52 for both sexes. As for BMI, the values were 24.9 kg/m2 and 0.53 in prediction of alteration BP and 25 kg/m2 and 0.53 in predicting GI. Conclusions: Despite the high prevalence of overweight identified between men and central obesity among women, satisfaction with body image was high in both sexes. These findings, together with the observed low correlation between nutritional status and real and ideal self-image suggests that it is possible that among the Khisêdjê, the ideal body shape is the one with the larger body size compared to the idealized in Western populations. The best cutoff points for discriminating the presence of GI and alteration BP among PIX Indians were close to recommended for the WC and similar to those recommended for BMI. However, both WC and BMI had low discriminatory power in predicting two outcomes in question.